Rancangan Sistem Keuangan Digital untuk Meningkatkan Kualitas Manajemen di Pondok Modern Daarul abroor - Arif budianto; Tata sutabri (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Islamic boarding schools (pondok pesantren) play a crucial role as educational institutions in shaping the character and academic quality of students. However, financial management in these institutions, especially in handling student funds, often faces challenges such as manual record-keeping, transparency issues, and process inefficiency. Therefore, this study aims to design a Smart System as a technological solution for managing student finances at Pondok Modern Daarul Abror. This system is expected to enhance financial administrative efficiency, improve recording accuracy, and provide easy access to financial information for students and the school management. The research methods used include needs analysis, system design, and system testing. The findings indicate that implementing a smart financial system in Islamic boarding schools not only accelerates administrative processes but also increases financial transparency, thus supporting efforts to improve the quality of services and education in the school.